Ex Libris Ryszard Stryjec : Gdańsk 1974 / Stryjec. - Stryjec, Ryszard (1932-1997) ([wydawca nieznany], 1974)
Na tle gór siedząca postać, u góry napis: Gdańsk 1974, u dołu: Ex Libris Ryszard Stryjec. Pod wyobrażeniem autograf autora.